Intra-Articular Injection of Umbilical Cord Mesenchymal Stem Cells Loaded With Graphene Oxide Granular Lubrication Ameliorates Inflammatory Responses and Osteoporosis of the Subchondral Bone in Rabbits of Modified Papain-Induced Osteoarthritis - Liu, Aifeng; Chen, Jixin; Zhang, Juntao; Zhang, Chao; Zhou, Qinxin; Niu, Puyu; Yuan, Ye (Frontiers in Endocrinology, 2022)
Aim: This study is to investigate the effects of umbilical cord mesenchymal stem cells (UCMSCs) loaded with the graphene oxide (GO) granular lubrication on ameliorating inflammatory responses and osteoporosis of the subchondral bone in knee osteoarthritis (KOA) animal models. Methods: The KOA animal models were established using modified papain joint injection. 24 male New Zealand rabbits were classified into the blank control group, GO group, UCMSCs group, and UCMSCs + GO group, respectively. The concentration in serum and articular fluid nitric oxide (NO), interleukin-6 (IL-6), tumor necrosis factor (TNF-α), type II collagen (COL-II), and glycosaminoglycan (GAG) was detected using ELISA, followed by the dissection of femoral condyles and staining of HE and Micro-CT for observation via the microscope. Results: GO granular lubrication and UCMSCs repaired the KOA animal models. NO, IL-6, TNF- α, GAG, and COL-II showed optimal improvement performance in the GO + UCMSCs group, with statistical significance in contrast to the blank group (P <0.01). Whereas, there was a great difference in levels of inflammatory factors in serum and joint fluid. Micro-CT scan results revealed the greatest efficacy of the GO+UCMSCs group in improving joint surface damage and subchondral bone osteoporosis. HE staining pathology for femoral condyles revealed that the cartilage repair effect in GO + UCMSCs, UCMSCs, GO, and blank groups were graded down. Conclusion: UCMSCs loaded with graphene oxide granular lubrication can promote the secretion of chondrocytes, reduce the level of joint inflammation, ameliorate osteoporosis of the subchondral bone, and facilitate cartilage repair.